دور اللغة العربية في عصر العولمة وتطبيقها في تطوير العلوم - Dihyatun Masqon (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2018)
This article aims to describe: 1) the role of Arabic language, 2) the interaction of Arabic with other living languages, 3) the linguistic growth methods possessed by the Arabic language, and 4) Some of the basics in teaching Arabic language for non-native speakers.